The Laboratory Diagnosis of Trichomonas vaginalis. Issue 1 (2005) - Garber, Gary E
Abstract : Trichomonas vaginalis, a parasitic protozoa that causes the sexually transmitted infection trichomoniasis, is the sexually transmitted infection with the largest annual incidence, exceeding 170 million cases per year. The disease can be difficult to diagnose due to its heterogeneous presentation and problems with diagnostic testing. All diagnostic tests are fraught with imperfections, but the old, reliable wet mount examination (in trained hands), and the newer InPouch method may be advantageous due to simplicity in technology and cost. The present article reviews the pros and cons of culture, antibody and nucleic acid-based technologies that may point to future diagnostic advances.